A rare cause of upper gastrointestinal hemorrhage: chronic thrombosis of the splenic artery - Arslan, Sevtap; Onur, Mehmet Ruhi; Akpınar, Erhan (Turkish Journal of Gastroenterology, 2017)
Abstract Upper gastrointestinal bleeding (UGIB) represents one of the most serious conditions of the gastrointestinal tract with a mortality rate of 10%. The main cause of UGIB is peptic ulcer, accounting for 28%-59% of cases. A rare cause of UGIB is submucosal arterial collaterals, which develop after splenic artery thrombosis. UGIB secondary to gastric submucosal collateral arteries should be considered in patients with endoscopic appearance of varicose veins in the absence of portal hypertension. Computed tomography angiography (CTA) is the only fast and noninvasive definitive imaging technique for such patients.